2022
DOI: 10.3389/fcimb.2022.962944
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of extracellular vesicles from red cells infected with Babesia divergens and Babesia microti

Abstract: Babesiosis is a zoonosis and an important blood-borne human parasitic infection that has gained attention because of its growing infection rate in humans by transfer from animal reservoirs. Babesia represents a potential threat to the blood supply because asymptomatic infections in man are common, and blood from such donors can cause severe disease in certain recipients. Extracellular vesicles (EVs) are vesicles released by cells that contain a complex mixture of proteins, lipids, glycans, and genetic informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
2
2
0
Order By: Relevance
“…However, by employing ultracentrifugation and the Exo-Quick approach, we were able to purify extracellular vesicles (EVs) that contained these parasite proteins. The EVs containing these B. duncani proteins may play a crucial role in the trafficking and delivery of these proteins, allowing them to be expressed on the outer membrane of infected RBCs similar to that reported for B. microti (30,38). Our IFA results, from in vitro B. duncani-infected parasites, further support the cellular distribution of these proteins.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, by employing ultracentrifugation and the Exo-Quick approach, we were able to purify extracellular vesicles (EVs) that contained these parasite proteins. The EVs containing these B. duncani proteins may play a crucial role in the trafficking and delivery of these proteins, allowing them to be expressed on the outer membrane of infected RBCs similar to that reported for B. microti (30,38). Our IFA results, from in vitro B. duncani-infected parasites, further support the cellular distribution of these proteins.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies in B. microti and B. divergens have demonstrated that several proteins of these parasites’ are actively exported by using vesicular-mediated export mechanisms (30, 38). To assess the mode of export of BdV234 and BdV38, the culture S and H fractions of B. duncani- infected human erythrocytes, as well as the Pl and H fractions of B. duncani -infected mice were subjected to ultracentrifugation at 120,000 x g for 14h at 4°C to separate the soluble (Us/UHs) and vesicle-associated membrane (Up/UHp) fractions.…”
Section: Resultsmentioning
confidence: 99%
“…These approaches combined with proteomics will help us gain a better understanding of the protein composition and biogenesis of vesicles secreted from Babesia iRBCs to the extracellular environment. The finding that the overall concentrations of EVs in 167K pellets were higher as a result of infection has also been observed with B. divergens (Beri et al, 2022), suggesting that Babesia infection modulates microvesicle generation in RBCs as reported with Plasmodium (Mantel et al, 2013).…”
Section: B Microti Irbcs Cultured In Vitro Release Evs Harboring the ...supporting
confidence: 58%
“…It has been postulated that this system of vesicles extending from the parasite into the RBC represents a novel mechanism of protein trafficking and export (Thekkiniath et al, 2019). Importantly, the vesicle-mediated protein export is not only restricted to the host RBC but also to the extracellular environment, as shown by the detection of B. microti immunodominant antigens in EVs isolated from the plasma of infected mice (Beri et al, 2022; Thekkiniath et al, 2019). A recent report by Beri et al identified EVs released from RBCs infected in vitro with B. divergens (Beri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%